Reduction of Liver Fibrosis After Treatment with Elbasvir/Grazoprevir in Patients with Hepatitis C Infection in Chronic Kidney Disease on Hemodialysis, a Quasi-Experimental Study - Bayu Laksono; Nenny Agustanti; Rudi Supriyadi; Muhammad Begawan Bestari; Siti Aminah Abdurachman (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Background: Approximately 5-60% of hemodialysis patients have comorbid of hepatitis C virus (HCV) infection. The survival rate of hemodialysis patients HCV is lower than those without HCV due to the risk of liver fibrosis and cardiovascular disease. The combination of Elbasvir and Grazoprevir is the drug of choice for these patients with HCV genotype 1 and 4 which mainly inherited in populations in Indonesia. However, a high cost is required for this genome testing.  Eradication of HCV might reduce liver fibrosis. One of the methods to evaluate liver fibrosis is by using APRI score. The aim of this study is to assess liver fibrosis using APRI score after  Elbasvir/Grazoprevir therapy completion.Method: This was a quasi-experimental study without a control group which conducted during April-November 2019 in Dr. Hasan Sadikin Hospital, Bandung. Patients with reactive anti HCV, detected HCV RNA without genotype test, and sustained virological response (SVR) 12 achieved were included. APRI score and HCV RNA tests were performed before and after 12 weeks end of therapy (SVR12). The data were analyzed using paired T-test at a 95% confidence level.Results: Approximately 30% of hemodialysis patients had HCV infection. A total of 37 HCV patients in the hemodialysis unit were given Elbasvir/Grazoprevir for 12 weeks. The APRI score before and after 12 weeks after therapy were 0.336 and 0.270 (p = 0.002) respectively.Conclusion: The combination of Elbasvir/Grazoprevir might reduce the degree of liver fibrosis based on APRI score from 0.336 to 0.270  in HCV patients with chronic kidney disease on hemodialysis